2017
DOI: 10.11159/tann17.111
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanocomposite of Functionalized Graphene Oxide with Multi Core-Shell Fe3O4-ZnO-TiO2 Nanoparticles

Abstract: -This project involves development and characterization of nanocomposite of functionalized graphene oxide with multi coreshell Fe3O4-ZnO-TiO2 nanoparticles (abbreviated as G-MCSN) with enhanced multi-functional properties. The multi core-shell nanoparticles consist of superparamagnetic core with modified shells of photocatalytic materials. After synthesis of Fe3O4 nanoparticles (using co-precipitation and solvothermal processes), it was coated with multi shells of ZnO and TiO2 (via a facile sol-gel rout). Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…3b). The result was in close agreement with previous experimental results (Nemati et al 2017). TiO2 particles (Fig.…”
Section: Morphology Characterizationsupporting
confidence: 93%
See 1 more Smart Citation
“…3b). The result was in close agreement with previous experimental results (Nemati et al 2017). TiO2 particles (Fig.…”
Section: Morphology Characterizationsupporting
confidence: 93%
“…101), ( 102), ( 110), ( 103), and (112). These results illustrated that the ZnO-Fe3O4 composite was successfully synthesized (Saffari et al 2015;Nemati et al 2017).…”
Section: Xrd Pattern Analysismentioning
confidence: 59%
“…Such functionalization of the surface of NPs can be achieved by coating them with a protective shell around the magnetic core. It has been reported that can be easily coated on Fe 3 O 4 as a protective layer [17]. ZnO has also been reported to show enhanced activity for desulfurization [18], and it is also a porous nanomaterial as well as a good photocatalytic material.…”
Section: Introductionmentioning
confidence: 99%